Aplikasi Whatsapp Sebagai Media Marketing Digital Untuk Mempromosikan dan Meningkatkan Produktifitas Kue Kacang Sari Rasa Prima - Prasadhya, Ignatius Bias Galih; Nggili, Ricky Arnold; Junaldo, Junaldo; Angga, Dedi Rob (Multidisciplinary Journal of Education , Economic and Culture, 2024)
This research aims to see the application of the Whatapps application in reaching consumers of the Sari Rasa Prima Nut Cake Business, and increasing business profitability. The method used is a qualitative research method, with data collection techniques through in-depth interviews and observation. With data obtained from several sources, it was concluded that the Whatapps (WA) application can be used to build good interpersonal relationships with consumers. There is certainty and accuracy in managing information from consumers. This ensures that trust is always maintained between producers and consumers. However, one of the obstacles faced is that the numbers used in WA are private and limited to use. This research shows that the use of the WA application can increase profits for producers of the Sari Rasa Prima Nut Cake Business, as well as build trust with consumers